MARTAND SUN TEMPLE OF KASHMIR VALLEY THROUGH THE AGES - Shabir Ahmad Lone; Prince Raina; Mohammad Ishaq Lone; E. Ravi (PT. Radja Intercontinental Publishing, 2024)
A Hindu temple devoted to Surya, the Martand Sun Temple (also called Pandou Laidan) dates back to the eighth century. Its building was ordered by the third Karkota Dynasty emperor, Lalitaditya Muktapida. Unfortunately, Sikandar Shah Miri, the Muslim monarch, demolished it, and it is now in ruins. The temple, located in Jammu and Kashmir five miles from Anantnag, had a fusion of Chinese, Gandharan, and Gupta architectural styles. It is known as Kartanda (Sun Temple) and is a centrally protected monument. The author draws attention to the remnants of the Kashmir Valley's Martand Sun Temple.